Pelatihan Teknik Pengambilan Gambar Melalui Smartphone : Pada Karang Taruna RT 04 Mustikajaya Bekasi - Selvy M Widuhung; Achmad Haikal; Rawit Sartika; Haryo Windratno (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Karang Taruna (a youth organization) activities are a form of participation of the younger generation in empowering their knowledge and skill to help the environment. Even though it is only on a small scale, according to their regions, if managed properly, a youth group like this can be beneficial for the community. Like the Karang Taruna RT 04 Mustikajaya Bekasi which in its activities focuses on helping the surrounding community by contributing positively to the interests of the environment, such as making murals on the walls of the RT post, to social activities that have an impact on residents. Realized the importance role of the younger generation in society, we are collaborating with Karang Taruna RT 04 Mustikajaya Bekasi to become partners in this Semester in our Community Service activity as lecturer in Bina Sarana Informatika University. Unfortunately the Karang Taruna not have social media like Instagram yet to post their activities and sharing some informations. One of the reason is becouse lack of skill of photograpic, that’s why thay felt not confident. We offer a solution by providing training on shooting techniques through smartphones, so that the resulting photos become more aesthetic and attractive. With good photo skills, it can attract other teenagers to join and do things that are beneficial for the environment.